Water quality of the inner Puno Bay, Titicaca Lake, during summer 2011 - Beltrán Farfán, Diana F. (2015)
Water quality of the inner Puno Bay was evaluated; we established 12 stations, and were assessed monthly from December 2010 to April 2011. Physicochemical water parameters were determined with EPA and APHA standard methods. Nutrients were determined spectrophotometrically. The parameters of temperature, dissolved oxygen, pH, phosphates, nitrates and nitrites of water show that the outlet of the stabilization lagoon of Puno City (Espinar Island) is a critical area of contamination at the inner Puno Bay. Transparency values were low. The electrical conductivity of water showed high values. Alkalinity values were high (75 - 150 mg/L) and very high (> 150 mg/L), indicating a high content of carbonates and bicarbonates. Water hardness were high (121-180 mg/L) and very high (> 180 mg/L). High levels of fecal coliform in waters near the island Espinar would be the result of wastewater discharges from the Puno city, without proper treatment.